(untitled) (Journal of the College of Basic Education, 2025)
This research addresses the topic of Diyyah (Blood Money) and its Rulings in the Holy Qur’an, focusing on its applications through the book “Al-Wafi.” The research aims to explain the concept of Diyyah in Islam, its types, and the associated Islamic rulings as stated in the Qur’anic verses and the Sunnah. It also highlights the wisdom behind legislating Diyyah, its role in achieving social justice, deterring crime, and preserving human life. The research is structured into four main sections: First Section: Definition of Diyyah and its legal foundation, explaining its meaning and references in the Qur’an. Second Section: Types of Diyyah and its rulings, including Diyyah for life and injuries, with distinctions between aggravated and reduced forms. Third Section: Aggravation of Diyyah and its impact, addressing reasons, time, and place, as well as its role in deterrence and justice. Fourth Section: The impact of Diyyah on achieving social justice, emphasizing its role in fostering social solidarity, preventing revenge, and resolving disputes. The study concludes that Diyyah is a comprehensive legal system aimed at deterrence, compensation, and safeguarding human dignity, exemplifying the inclusiveness and justice of Islamic Sharia